Alcune riflessioni sulla teologia e il suo metodo secondo i recenti documenti della Chiesa - Ladaria, S.I., Mons. Luis F. (Alpha Omega, 2017)
Summary: What is theology? The author wishes to offer some elements of response to this question on the basis of recent Church documents. He begins by analysing the definition: ‘Theology is the scientific reflection upon divine revelation, which the Church accepts as universal salvific truth by way of the faith’ (CTI: Theology today). He proceeds by reviewing different key aspects of theology: the centrality of the mystery of Christ, who acts even today in the Church (Optatam totius). The written Word of God as foundation and soul of theology, as well as sacred Tradition (Dei Verbum). The two inseparable dimensions of doing theology: the auditus fidei and the intellectus fidei (Fides et ratio). The Magisterium, the authoritative custodian of the Church’s faith, as an intrinsic element of theology (Donum veritatis). The humble task of guarding and of deepening the faith of the simple (Lumen fidei). Finally, the author puts forward some of the tasks facing theology today: Attention to the rationality of theology, openness to, and constant exchange with, the world, the unity of theology within the plurality of its methods and of its disciplines, theology of ‘wisdom’, connected once more to spiritual wisdom and to the experience of the saints. Key words: theology, theologians, current theology, theological method, Magisterium, Church, faith, ecclesiastical documents. Parole chiave: teologia, teologo, teologia odierna, metodo teologico, magistero, Chiesa, fede, documenti ecclesiastici.